2016
DOI: 10.1097/md.0000000000005038
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality predictivity of nutritional assessment tools in the postoperative care unit

Abstract: The aim was to evaluate the nutritional situation of patients admitted to the Postoperative Acute Care Unit using classic methods of objective anthropometry, systemic evaluation methods, and Nutrition Risk in Critically Ill (NUTRIC) score, and to compare them as a predictor of morbidity and mortality.At admission to the postoperative care unit, patients undergoing various surgeries were assessed for the following items: Subjective Global Assessment (SGA), Nutritional Risk Index (NRI), Nutritional Risk Screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 34 publications
10
38
0
Order By: Relevance
“…This could indicate a poor match between anthropometric measurements and the risk classifications of the NRS tools. Previous studies also suggested that there was no correlation between BMI and clinical outcomes [14,15]. Weight gain and weight loss are not reliable indicators of body composition changes due to fluid collection, such as ascites or body edema.…”
Section: Discussionmentioning
confidence: 97%
“…This could indicate a poor match between anthropometric measurements and the risk classifications of the NRS tools. Previous studies also suggested that there was no correlation between BMI and clinical outcomes [14,15]. Weight gain and weight loss are not reliable indicators of body composition changes due to fluid collection, such as ascites or body edema.…”
Section: Discussionmentioning
confidence: 97%
“…With respect to mortality predictivity of NRS‐2002 in the ICU setting, a Turkish study conducted by Özbilgin et al with 152 patients, found a difference of 1.3 points in NRS‐2002 scores (4.56 ± 2.24 vs 5.86 ± 2.34; P ‐value = .026) between survivors and non‐survivors, respectively, on the 28th day. The mean NRS‐2002 values agree with the cut‐off points proposed by ASPEN and corroborate with our results.…”
Section: Discussionmentioning
confidence: 99%
“…An NRS score >3 or NUTRIC score >5 indicate nutrition risk. The subjective global assessment evaluates nutrition status; however, the NRS 2002 and NUTRIC scores take into account both nutrition status and disease severity, with higher scores correlating with higher mortality . The NUTRIC score is limited by the need for an interleukin‐6 (IL‐6) level.…”
Section: Process‐related Barriersmentioning
confidence: 99%
“…The subjective global assessment evaluates nutrition status; however, the NRS 2002 and NUTRIC scores take into account both nutrition status and disease severity, with higher scores correlating with higher mortality. 13,14 The NUTRIC score is limited by the need for an interleukin-6 (IL-6) level. The modified NUTRIC score was developed and excludes an IL-6 and independently predicts 28-day mortality.…”
Section: Process-related Barriersmentioning
confidence: 99%